178k views
2 votes
If f(x)=3^x+10x and g(x)=2x-4, find (f-g)(x)

2 Answers

5 votes

Answer: 3^x +8x + 4

a p e x

Explanation:

take the parentheses

If f(x)=3^x+10x and g(x)=2x-4, find (f-g)(x)-example-1
User Matthew Sandoz
by
5.5k points
2 votes

Answer:

(f-g)(x) = f(x) - g(x) = 3^x + 10x - (2x - 4) = 3^x + 10x - 2x + 4 = 3^x + 8x + 4;

Explanation:

User Abraham Mathew
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.